Phenological development and production potential of different cultivars of holy basil (Ocimum sanctum L.) in lower hills of Uttarakhand (Current Horticulture, 2024)
The experiment conducted at CSIR-Central Institute of Medicinal and Aromatic Plants Research Centre in Purara, Bageshwar,  Uttarakhand, India aimed to compare the phenological development and production potential of seven varieties of holy basil  (Ocimum sanctum L.). The varieties tested were CIM-Jyoti, CIM-Surabhi, CIM-Snigdha, CIM-Saumya, CIM-Ayu, CIM-Sharada,  and CIM-Angna. The experiment followed a randomized block design with three replications. The study focused on observing  plant growth characteristics, yield, oil composition, and dry herb production in the lower hills of the Western Himalayan region  in Uttarakhand. Among the seven varieties tested, CIM-Ayu performed the best in terms of growth and yield parameters, except  for plant height. CIM-Surabhi had the highest seed yield, while CIM-Ayu had the highest dry herb yield and oil production.
Keywords: Varieties; Essential oil; Morphology; Growth; Plant height; Herb yield; Dry herb